Managing End-User Satisfaction and Compliance during OS Migrations in Multinational Research Organizations - Graveau, Julien (My University, 2025)
This thesis investigates how structured IT governance frameworks can support end-user compliance and satisfaction during operating system (OS) migrations, focusing on the case of ITER’s transition from Windows 10 to Windows 11. While existing governance models such as COBIT and ITIL provide structured guidance for managing risk and standardizing processes, their application during OS migrations remains underexplored. The study addresses this gap through a mixed methods case study, combining the analysis of 176 service desk tickets with seven semi-structured interviews conducted across IT and non-IT roles. The findings reveal that compliance emerged through negotiated behaviours shaped by user perception of change, and that workarounds bordering on non-compliance were also part of a healthy approach to change. While technical execution greatly improved over time, some persistent gaps in perspectives between end users and managers were observed. The study proposes that integrating governance frameworks with change management models (such as ADKAR and Kotter) enables organizations to adapt formal controls to contextual realities. This approach is especially relevant in multinational scientific institutions, where strict compliance requirements coexist with diverse user expectations and operational constraints.
Keywords: IT governance, end-user compliance, OS migration, change management, Windows 11, ITER